Factors Affecting the Area of Paddy Field on the Island of Sumatra 2015-2022 - Rohdy Andika; Handoko Hadiyanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to identify the factors of the number of industries (X1), population (X2) and gross regional domestic product (GRDP) (X3) that affect the area of paddy fields (Y) on the island of Sumatra. The scope of this survey includes 10 provinces on the island of Sumatra.The data used is secondary data derived from BPS and uses panel data type. The analysis method used in this study uses multiple linear regression analysis with SPSS 25 analysis tool. The results of the study indicate that there is a positive relationship between the variables of the number of industries and the number of population with the area of paddy fields, while GRDP has a significant negative effect on the area of paddy fields. These results indicate that an increase in population and industry makes the need for paddy fields also increase while an increase in GRDP will make a decrease in the area of paddy fields.